Diagnostic Value of Sural Nerve Biopsy: Retrospective Analysis of Clinical Cases From 1981 to 2017 - Prada, Valeria; Massucco, Sara; Venturi, Consuelo; Geroldi, Alessandro; Bellone, Emilia; Mandich, Paola; Minuto, Michele; Varaldo, Emanuela; Mancardi, Giovanni; Grandis, Marina; Schenone, Angelo (Frontiers in Neurology, 2019)
Nerve biopsy represents the conclusive step in the diagnostic work-up of peripheral neuropathies, and its diagnostic yield is still debated. The aim of this study is to consider the impact of nerve biopsy on reaching a useful diagnosis in different peripheral neuropathies and its changing over time. We retrospectively analyzed 1179 sural nerve biopsies performed in the period 1981-2017 at Neurological Clinic of Policlinico San Martino (Genoa). We relied on medical records and collected both clinical and pathological data in a database. Biopsy provided univocal diagnoses in 53% of cases (with an increase over time), multiple diagnostic options in 14%, while diagnosis was undetermined in 33% (undetermined reports decreased during the years). In 57% of patients, the pre-biopsy suspicion was confirmed, while in 43% sural biopsy modified the clinical diagnosis. The highest yield was in axonal neuropathies (29% undetermined reports versus 40% in demyelinating and 48% in mixed neuropathies). In 68% of patients with vasculitic neuropathy, this etiology was already suspected, whereas in 32% nerve biopsy modified the clinical diagnosis. During the years, the number of annually performed biopsies decreased significantly (p=0.007), with an increase in the mean age of patients (p<0.0001). The percentage of hereditary neuropathies had a significant decrease (p=0.016), while the rate of vasculitic and chronic inflammatory neuropathies increased (p<0.0001). This is the largest Italian study addressing the yield of sural nerve biopsy. During the years, we observed a progressive refinement of the indication of this procedure, which confirms its utility for interstitial neuropathies, particularly if non-systemic vasculitic neuropathy is suspected.